2021
DOI: 10.1186/s13229-021-00473-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in CACNA1E found in patients with intellectual disability, developmental regression and social cognition deficit but no seizures

Abstract: Background De novo variants in the voltage-gated calcium channel subunit α1 E gene (CACNA1E) have been described as causative of epileptic encephalopathy with contractures, macrocephaly and dyskinesias. Methods Following the observation of an index patient with developmental delay and autism spectrum disorder (ASD) without seizures who had a de novo deleterious CACNA1E variant, we screened GeneMatcher for other individuals with CACNA1E variants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…VGCCs are transmembrane proteins activated in response to the depolarization of the cell membrane, and they mediate the flux of calcium ions into excitable cells [ 71 , 72 ]. These genes are highly associated with various mental disorder phenotypes, such as neurodevelopmental disorders, intellectual disability, bipolar disorder, anxiety, and depression [ 73 , 74 ], and there is increasing evidence that CACNA1C expression in the brain directly regulates depression-related behaviors [ 72 ]. Interestingly, the genetic risk variants of mental disorders in CACNA1C act as both mQTLs and eQTLs; therefore, the genotype at these risk SNPs is associated with a variation in DNAm and expression levels of the gene [ 56 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…VGCCs are transmembrane proteins activated in response to the depolarization of the cell membrane, and they mediate the flux of calcium ions into excitable cells [ 71 , 72 ]. These genes are highly associated with various mental disorder phenotypes, such as neurodevelopmental disorders, intellectual disability, bipolar disorder, anxiety, and depression [ 73 , 74 ], and there is increasing evidence that CACNA1C expression in the brain directly regulates depression-related behaviors [ 72 ]. Interestingly, the genetic risk variants of mental disorders in CACNA1C act as both mQTLs and eQTLs; therefore, the genotype at these risk SNPs is associated with a variation in DNAm and expression levels of the gene [ 56 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CACNA1A gene encodes a subunit of the voltage-dependent P/Q-type calcium channel α-1A (Zhang et al 2020b ), and the CACNA1E gene encodes a subunit of the voltage-dependent R-type calcium channel α-1E (Helbig et al 2018 ). These genes are widely expressed throughout the central nervous system and are strongly associated with epilepsy and intellectual developmental disorders (Hommersom et al 2021 ; Royer-Bertrand et al 2021 ). In addition, CACNA1E is of potential therapeutic value in non-small cell lung cancer (Gao et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, case studies on three of the newly identified genes -AGO1, CACNA1C, and CACNA1E -have been published. [25][26][27] NeuroDev participants comprised the only geographic African cases in any of the case series reports, and NeuroDev will be the first African NDD cohort to contribute, at scale, to rare disease discovery activities. As described by the NHGRI Atlas of Human Malformations initiative, syndromic NDDs often vary in their phenotypic presentation between ancestral groups 28 , a phenomenon particularly well documented with regard to canonical facial features.…”
Section: Genetic Analyses Of the Trio Pilot Datamentioning
confidence: 99%
“…To date, case studies on three of these genes -AGO1, CACNA1C, and CACNA1Ehave been published. [28][29][30] These variants may potentially be reclassified after re-evaluation over time.…”
Section: Genetic Analyses Of the Trio Pilot Datamentioning
confidence: 99%